2006
DOI: 10.1089/end.2006.20.1060
|View full text |Cite
|
Sign up to set email alerts
|

A 4-Year Review of Balloon Dilation of Ureteral Strictures in Renal Allografts

Abstract: Definitive surgical management should be considered if obstruction persists after one attempt at ureteral dilation, as multiple dilations have a low success rate (25%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 2 publications
0
19
1
1
Order By: Relevance
“…In 2 cases, endoscopic dilation was applied. This technique is seldom used because it has a low success rate and a high recurrence rate compared with open technique, especially if the obstructive lesion is relatively long [7][8][9] . All urological complications after revision of the ureterovesical anastomosis occurred in patients who had undergone neoureterocystostomy.…”
Section: Discussionmentioning
confidence: 99%
“…In 2 cases, endoscopic dilation was applied. This technique is seldom used because it has a low success rate and a high recurrence rate compared with open technique, especially if the obstructive lesion is relatively long [7][8][9] . All urological complications after revision of the ureterovesical anastomosis occurred in patients who had undergone neoureterocystostomy.…”
Section: Discussionmentioning
confidence: 99%
“…[9] reported that 13 patients underwent dilatation with (nine patients) or with no (four) diathermic incision, only the four patients treated with dilatation had recurrent obstruction, while the nine treated with dilatation and incision had no obstruction recurrence (mean follow-up 58 months, range there was no recurrence of obstruction in six of eight patients. The outcomes of published reports (with more than five patients) on endoscopic management for ureteric obstruction in transplanted kidneys are summarized in Table 2 [6,7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The total long-term success rate was 68%.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Bromwich et al . [23] reported that the success rate of repeated multiple balloon dilatations for ureteric strictures in renal allografts was only 25%, they also recommended that definitive surgical management should be considered if a first dilatation fails.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported success rate after initial ureteroplasty with a plain balloon is low in the literature, between 45% and 58% 3,8 . The success rate is even lower following subsequent ureteroplasty for persistent stricture 9 …”
Section: Introductionmentioning
confidence: 96%